A technoeconomic assessment of microalgal culture technology implementation for combined wastewater treatment and CO2 mitigation in the Arabian Gulf - Al Ketife, Ahmed M. D.; Almomani, Fares A.; El-Naas, Muftah; Judd, Simon J. (Elsevier, 2019)
A technoeconomic assessment (TEA) has been conducted of the feasibility of large-scale application of microalgal culture technology (MCT) to the combined mitigation of CO2 emissions from flue gases and nutrient discharges from wastewater in the Arabian Gulf. The assessment has incorporated the selection of the algal species and MCT technologies, the extent of nutrient removal, and the biomass/biofuel production rate. The cost benefit of the abatement of pollutants (in the form of CO2 and nutrient discharges) was included by assigning appropriate credits to these contributions. The overall economic viability was quantified as the break-even selling price (BESP) of the generated biocrude, taken to be the price at which the product must sell to cover the operating expenditure (OPEX). Based on available information and optimal operational conditions, the BESP was calculated as being $0.544 per kg biomass, equating to $0.9 L−1 for the extracted biocrude, the credited items contributing ˜14% of this figure. The BESP was found to be most sensitive to the algal growth rate μ, the BESP changing by ±24% in response to a ±20% change in μ. Whilst the terms of reference of the study are limited to OPEX contributors, the potential for sustainability associated with the innately reliably high levels of natural light in the Gulf region appear to provide auspicious circumstances for large-scale implementation of MCT. For emerging economies with a comparable climate but without a mineral oil-based economy a greater financial benefit from the proposed scheme would arise.
Keywords: Technoeconomic analysis; Microalgae culture technology; Break-Even selling price; Large-Scale implementation; carbondioxide biofixation; Nutrient removal